Red wolf : a novel - Marklund, Liza, 1962- (Atria Books, 2011)
Stockholm journalist Annika Bengtzon turns independent reporter, mostly pursuing terrorism stories. While she's investigating in the northern town of Luleå̊, a fellow journalist and source dies in a hit-and-run accident, which turns out to be the first in a series of murders. Annika traces these murders to a deadly act of sabotage on a Swedish military base in 1969, and begins to suspect that the man behind the present-day slayings and the army attack--known only by his code name of "Ragnwald"--has returned to kill again.